Calcite twins, their geometry, appearance and significance as stress-strain markers and indicators of tectonic regime : a review - Burkhard, Martin (My University, 1993)
Twin lamellae are a widespread feature in calcites of any type and origin. Twinning in calcite is an important intracrystalline deformation mechanism with low critical resolved shear stress and virtually no temperature dependence. In contrast to most slip systems in rock-forming minerals, twinning therefore permits intracrystalline deformation at very low temperature and very little confining pressure. Twinning alone, however, cannot lead to large strains because only one independent slip system is effectively available. Twins lead to discontinuous shearing on the grain scale which gives rise to considerable strain incompatibilities at grain boundaries. Twinning consequently leads to strain hardening. Detailed observations of the geometry of twin lamellae show that incompatibilities at grain boundaries are eliminated by pressure solution on the grain scale at low temperature and dynamic recovery processes at higher temperatures.
Twins are found in various tectonic environments and record very small strains in rocks deformed under very little cover. Different twinning strain and twinning stress methods and palaeopiezometers are critically reviewed. All methods are limited to strains of less than 15% shortening (or extension) by twinning. Twinning nevertheless is an important, although not directly measurable, contribution to the total strain in highly strained calcite rocks at least up to middle greenschist facies, under which conditions it is the most effective contributor to the formation of strong lattice preferred orientations in calcite tectonites.
The appearance of calcite twin lamellae changes systematically as a function of deformation temperature. Micro-twins and straight narrow (< 1 μm) lamellae are characteristic of very low temperatures where no other slip system competes and where the absence of effective recovery mechanisms prohibits large strains by twinning. Above ca 150°C, thicker (> 1−5 μm) but fewer twins are developed. Above approximately 200°C, curved twins, twinned twins and completely twinned grains indicate the progressive importance of other slip systems, and larger intracrystalline strains are possible. At ca 250°C and above ancient straight twin lamellae are modified into irregular geometries by recrystallization and grain-boundary migration. The appearance of calcite twins is proposed as an approximate but rapid and easy-to-use geothermometer in low-temperature environments.